2020
DOI: 10.1001/jamanetworkopen.2020.15205
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Internal Medicine Faculty by Sex and Race/Ethnicity, 1980-2018

Abstract: Key Points Question Did sex and racial/ethnic diversity in the academic internal medicine workforce between 1980 and 2018 reflect the changing demographic composition of the general population (in 2017) and medical student body? Findings This cross-sectional study used data on full-time medical school faculty appointed to US internal medicine departments from 1980 to 2018, matriculants to US medical schools from 1980 to 2018, and the general US population f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…Prior studies demonstrate the number of women and members of underrepresented groups in medicine (URM), such as American Indian or Alaskan Native, Black, Latino or Hispanic, and Native Hawaiian or other Pacific Islander individuals, are increasing throughout academic medicine. 1 , 2 However, little is known in the current literature regarding variation and trends in demographics of academic faculty across medical specialties or the retention of residents identifying as women or URM as academic faculty. This study adds to the literature by examining 30-year demographic trends across academic medicine departments and providing novel comparisons of the proportion of individuals identifying as women or URM between academic faculty and specialty-matched residents.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies demonstrate the number of women and members of underrepresented groups in medicine (URM), such as American Indian or Alaskan Native, Black, Latino or Hispanic, and Native Hawaiian or other Pacific Islander individuals, are increasing throughout academic medicine. 1 , 2 However, little is known in the current literature regarding variation and trends in demographics of academic faculty across medical specialties or the retention of residents identifying as women or URM as academic faculty. This study adds to the literature by examining 30-year demographic trends across academic medicine departments and providing novel comparisons of the proportion of individuals identifying as women or URM between academic faculty and specialty-matched residents.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to address these discrepancies should include improvement in recruitment, retention, and mentorship to ensure career satisfaction. 5 Initiating a mentoring relationship may be difficult, particularly for junior faculty and trainees. A previous research survey completed among faculty within our department found that only 30% of respondents identified a mentor.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Developing an oncology workforce that reflects the patients whom it serves has been a priority for both American Society of Clinical Oncology 11 and the National Cancer Institute (NCI), 12 as there are known gender and racial/ethnic gaps within the physician pipeline and workforce. 13 , 14 However, the leadership gap in cancer care remains largely unquantified and is a key component to understanding how institutions may prioritize equity, diversify hiring, and promote systemwide change to improve cancer disparities. This cross-sectional study was designed to evaluate the gender, racial, and ethnic makeup for the full leadership team of NCI-designated cancer centers and to compare this with the diversity of actively practicing physicians and with the city populations served by each center.…”
Section: Introductionmentioning
confidence: 99%